Legal self-defense for mental health practitioners : quality care and risk management strategies - Woody, Robert Henley (Springer Pub. Co., 2013)
At some point in their careers, mental health professionals may face legal action from clients. Clients may be noncompliant regarding policies agreed upon at the outset of therapeutic services, not adhere to an individualized treatment plan, be inappropriately aggressive, and file unjustified ethics and licensing complaints and/or lawsuits. Unfortunately, many mental health practitioners are not prepared for such actions and suffer great distress that affects their professional and personal lives. This practical text, written by an author who is both a psychologist and an attorney, demonstrate.